Targeting androgen receptor stability and degradation: approaches for developing a therapy for spinal and bulbar muscular atrophy - Riccardo Cristofani; Barbara Tedesco; Veronica Ferrari; Marta Chierichetti; Marta Cozzi; Paola Pramaggiore; Laura Cornaggia; Ali Mohamed; Elena Casarotto; Maria Brodnanova; Rocio Magdalena; Prashant Koshal; et al. (Cell Communication and Signaling)
Abstract Conformational changes of proteins can occur due to mutations or stress conditions, altering their functionality through loss of physiological or gain of pathological function. A Protein Quality Control (PQC) system exists in cells to deal with the accumulation of misfolded proteins and aggregates, comprising a network of chaperones and degradative pathways to refold or remove the aberrant proteins. Protein misfolding and PQC system impairment lead to a broad range of diseases, including neurodegenerative and neuromuscular disorders, among them spinal and bulbar muscular atrophy (SBMA). SBMA is a neuromuscular disorder caused by a polyglutamine expansion (polyQ) in the androgen receptor (AR) protein. Expanded AR (ARexp) is highly prone to misfolding and aggregation, leading to its accumulation in affected tissues. Here, we summarise the dynamics that control AR protein stability and its degradation in physiological conditions. Next, we recapitulate the current knowledge of the molecular mechanisms of SBMA pathogenesis involving the PQC system. Finally, we provide an overview of promising approaches to SBMA intervention involving the modulation of PQC system functions to reduce ARexp accumulation and its toxic effects in affected cells.